Media Interaktif Si Nana Pemberani untuk Pengenalan Coding dan Pengembangan Kemampuan Berpikir Kritis Anak Usia Dini - Rina Wijayanti; Akbar, Mochammad Ramli; Afnia, Bella Nur; Ahsan, Moh (Institut Nalanda, 2026)
The increasing use of digital technology among young children has been largely consumptive, focusing on watching YouTube, TikTok, and sending messages, with limited adaptive digital-based learning media for introducing coding concepts in early childhood education (ECE). This study aims to develop interactive media Nana the Brave as a tool to introduce coding concepts and enhance critical thinking skills in children aged 4–5 years. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The media was created with Canva and Articulate Storyline, featuring the main character “Nana” and a robot companion “Cappucina,” and included nine game-based activities covering algorithms, sequencing, problem-solving, and pattern recognition. A trial was conducted with 24 children in Group A at TK Muslimat NU 10 Pandanmulyo Tajinan, Malang Regency. Validation results indicated excellent feasibility, with ratings of 96% from material experts, 90% from media experts, and 95% from ECE practitioners. Implementation demonstrated that the media effectively stimulated children’s critical thinking skills, including classification of shapes and colors, pattern comparison, instruction comprehension, and simple problem-solving. The findings conclude that Nana the Brave is highly feasible for use in introducing coding concepts in early childhood learning and has strong potential to strengthen children’s digital literacy readiness from an early age.